Ideally human-ish: How anthropomorphized do you have to be in shopper-facing retail technology? - Barney, Christian; Hancock, Tyler; Esmark Jones, Carol L.; Kazandjian, Brett; Collier, Joel E. (Journal of retailing, 2022)
•The impact of anthropomorphized technology on shopper behavior has not been closely examined.•An anthropomorphized app can increase immersion, attitudes, and purchase intentions.•Cognitive (ability to think) and visual (looks) are different types of anthropomorphism.•The addition of a 2nd type of anthropomorphism will not increase immersion further. As shopper-facing retail technology (SFRT) increasingly replaces human interactions in retail environments, many businesses are considering how to make their retail technology more human-like. This paper identifies two methods of anthropomorphizing technology—visual and cognitive—and seeks to determine whether using these two types of anthropomorphism with a product/service is a better approach to interacting with consumers or whether a combination of visual and cognitive anthropomorphic features is less effective than one. This paper proposes that including one form of anthropomorphism in an SFRT may increase purchase intentions, while the addition of a second form of anthropomorphism will not lend an additional advantage. Specifically, the theory of social response is used to examine the process through which consumers view anthropomorphized SFRT. Three studies assess the proposed model in a mobile shopping application context and include the use of a functional app and 360° video experiments. Theoretical and practical implications are discussed. [Display omitted]